Relationship of Work Load to The Level of Work Stress Intensive Nurses At Al Ihsan Hospital, West Java Province, 2015 - M Iqbal Angga Kusuma (UPT PPM Sekolah Tinggi Ilmu Kesehatan Al Irsyad Al Islamiyyah Cilacap, 2021)
This research is motivated by many nurses who still experiencing high workload and high stress level of heavy work, especially among intensive nurses. Preliminary study with interviews to 10 nurses in Al Ihsan Hospital’s ICU and ICCU results with six nurses (60%) feel exhausted to work in the intensive room. Eight nurses are experiencing symptoms such as work stress often complained of headache, disorders of sleep patterns, and lethargic, and often feel anxiousness, irritability and restlessness. Eight nurses (80%) said the responsibility of nurses in the intensive is heavy as it relates to critical patient, patient's family demands and the use of tools supporting intensive patients. In addition there are some nurses who have not yet received training. The research aims to find out the relationship of workload toward intensive nurse stress level in the provincial hospital of Al Ihsan West Java Province. The design of the research is correlation survey of cross sectional approach. The number of samples as many as 22 managing nurses in Al Ihsan Hospital’s ICU and ICCU using total sampling techniques. Data collection using primary data by questionnaires. The results of the univariate analysis processed with data (frequency distribution) and bivariate (rank spearman). The results showed intensive nurse workload most are heavy (54,55%), moderate (36,4%), and lighter (9.1%). The level of intensive nurse's work stress most is being (86.4%) and lightweight (13.6%). There is a relationship with workload stress levels among intensive nurses who works in Al-Ihsan Hospital (p-value 0,010).